ChemInform Abstract: Environmetally Benign Michael and Claisen Schmidt Reaction of Aromatic Carbonyl Compounds by Alkaline Polyionic Resin. Issue 7 (18th February 2014) - Jaitak, Vikas; Kaul, V. K.; Das, Pralay
Abstract An alkaline, polystyrene‐supported ammonium salt is successfully applied as catalyst in regioselective Michael and Claisen—Schmidt reactions.